Bereaved in Me: Understanding the Vicarious Grief Experiences Among Helping Professionals During the COVID-19 Pandemic - Jose, Kaina Marie Clare Sera (Archīum Ateneo, 2023)
Literature on the experience of the bereaved during the COVID-19 pandemic suggests how complicated it has been for those who lost loved ones. However; the sense of grief experienced by those who journey with them is relatively unexplored. The present study examines vicarious experiences of grief of healthcare workers; faith-based workers and mental health workers who worked with the bereaved due to COVID-19 deaths. The study was done in two phases. In the first phase; a survey showed that compared to other helping professionals; healthcare workers reported the highest levels of vicarious grief. In the second phase; in-depth interviews revealed five themes: acknowledging contexts of grief; navigating relations with the bereaved; sharing others’ grief; internalizing encounters; and negotiating challenges. Findings highlight the need for supportive interventions at the organizational level.